The Impact of the COVID-19 Pandemic on Male Strength Athletes Who Use Non-prescribed Anabolic-Androgenic Steroids - Zoob Carter, Barnaby N.; Boardley, Ian D.; van de Ven, Katinka (Frontiers in Psychiatry, 2021)
Background: One sub-population potentially affected by the COVID-19 pandemic are strength athletes who use anabolic-androgenic steroids (AAS). We examined links between disruption in AAS use and training due to the pandemic and mental health outcomes in this population, hypothesising: a) the pandemic would be linked with reduced training and AAS use; and b) athletes perceiving greater impact on their training and AAS use would report increases in detrimental mental health outcomes. Methods: Male strength athletes using AAS (N = 237) from 42 countries completed an online questionnaire in May 2020. A sub-sample (N = 90) from 20 countries participated again four months later. The questionnaire assessed pre-pandemic and current AAS use and training, alongside several mental health outcomes. Results: At Time 1, most participants perceived an impact of the pandemic on AAS use (91.1%) and/or training (57.8%). Dependent t-tests demonstrated significant reductions in training frequency (t = 7.78; p <.001) and AAS dose (t = 6.44; p <.001) compared to pre-pandemic. Linear regression showed the impact of the pandemic on training was a significant positive predictor of excessive body checking (B = .35) and mood swings (B = .26), and AAS dose was a significant positive predictor of anxiety (B = .67), insomnia (B = .52), mood swings (B = .37). At Time 2, fewer participants perceived an impact of the pandemic on AAS use (29.9%) and/or training (66.7%) than at Time 1. Training frequency (t = 3.02; p < .01) and AAS dose (t = 2.11; p < .05) were depressed in comparison to pre-pandemic. However, AAS dose had increased compared to Time 1 (t = 2.11; p < .05). Linear regression showed the impact of the pandemic on training/AAS use did not significantly predict any mental-health outcomes. However, AAS dose was a significant negative predictor of depressive thoughts (B = - .83) and mood swings (B = -2.65). Conclusion: Our findings showed impact of the pandemic on the training and AAS use, reflected in reduced training frequency and AAS dose. However, whilst we detected some short-term consequential effects on mental health, these did not appear to be long-lasting.